Logam Berat Timbal (Pb) dan Efeknya pada Sistem Reproduksi - Kadek Yuniari Suryatini; I Gusti Ayu Rai (Emasains : Jurnal Edukasi Matematika dan Sains, 2018)
Lead is one of heavy metals that is highly toxic and widely known by the public. Lead causes the most poisoning of living things but is widely used in producing industrial products. The toxic effect of lead on the reproductive system causes a disruption of the spermatogenesis process thus affecting the quality of semen in the number, morphology, motility, and abnormal forms of spermatozoa. Heavy metal lead also has toxic effects on gametes and causes chromosomal defects. Lead exposure in women causes menstrual disorders, greater risk of miscarriage, fetal abnormalities, infant mortality, and premature delivery. Lead also causes infertility in men and women.